(3GdGNJUGU HPcQ YeGQI GdLHGfI GdJi gi eUdi GdYjOjf aj ebOe eOjfI UfYGA hYeGQI GdefGQJjf aj GdeSLO GdLGeY HUfYGAs - (3fXGe GdOjf EHQGgje Hf CHj HcQ Hf Ydj Hf eYGP Hf GdeHGQc Hf JHY Hf jhSa, GHf aVjds
(3ChdgG (B:s
(3hHYO aGf GdbUO hGdZQV PcQ JLOjO YeGQI GdLHGfg GdJi gi eUdi GdYjOjf s
(3BNQgG (B:s
(3hNQL ef ecI Edi Mfjf heYg GKfi YTQ Gda hGMO ef ghGRf ef GdCehGd eGdG JYO hdG JMUi s
(3fSNI eUhQI Yf fSNI HQSe MGce Gdjef TeS GdOjf Hf Ydi GdCafOi eMahXI HecJHI CjGUhajGs
(3hgh Pjd Ydi GdLRA GdKGdK ef JGQjN UfYGA Gdjef ddeDQN CHj GdYHGS CMeO Hf YHO Gddg Hf eMeO GdQGRi hGdeJhai SfI (B460s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B570 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B2803) s
Keywords: (3GdJGQjNs